2020
DOI: 10.1007/s12350-018-01471-4
|View full text |Cite
|
Sign up to set email alerts
|

Automated dynamic motion correction using normalized gradient fields for 82rubidium PET myocardial blood flow quantification

Abstract: Background.-Patient motion can lead to misalignment of left ventricular (LV) volumes-ofinterest (VOIs) and subsequently inaccurate quantification of myocardial blood flow (MBF) and flow reserve (MFR) from dynamic PET myocardial perfusion images. We aimed to develop an image-based 3D-automated motion-correction algorithm that corrects the full dynamic sequence for translational motion, especially in the early blood phase frames (~ first minute) where the injected tracer activity is transitioning from the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
2
32
1
Order By: Relevance
“…Motion magnitude was found larger in the stress studies than that in the rest studies. 1 In another study, the incidence and magnitude of motion reported in Ref. 7 were much larger than those reported in the current study.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…Motion magnitude was found larger in the stress studies than that in the rest studies. 1 In another study, the incidence and magnitude of motion reported in Ref. 7 were much larger than those reported in the current study.…”
contrasting
confidence: 62%
“…In a recent study, an 82 rubidium ( 82 Rb)-dynamic-tailored motion-correction framework has been proposed to address the voluntary body motion for all the dynamic frames, including both early and late phases. 1 This approach brings us one step closer to the practical and full motion correction for dynamic cardiac PET studies. In this editorial, we discussed the current status and limitations of motion-correction methods for dynamic cardiac PET, including the recent publication at JNC, and also pointed out the remaining challenges for future developments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Previously, Poitrasson-Rivière et al introduced an automated algorithm localizing the left and right ventricular blood pools in 4-D, with registration of each frame to a tissue reference image volume using normalized gradient fields. 22 This image-based, automated motion correction algorithm using normalized gradient fields applied to dynamic PET sequences matched the results of manual motion correction, reducing bias and variance in MBF and MFR. 22 It is also important to realize that motion correction must be practical in the clinical setting.…”
Section: See Related Article Pp 1104-1113mentioning
confidence: 81%
“…Evidence supporting this is the far greater fraction of stress studies containing motion than rest studies. 22,23 Proper reconstruction of images when the heart has shifted with respect to the attenuating organs is non-trivial.…”
Section: See Related Article Pp 1104-1113mentioning
confidence: 99%